MO138: The Level of Microrna Expression in Urine of Cynomolgus Monkeys, Who Received Diet Rich in Common Salt. (3rd May 2022) - Kayukov, Ivan; Zaraiski, Mikhail; Beresneva, Olga; Ivanova, Galina; Parastaeva, Marina; Kucher, Anatoly; Khasun, Mokhamad; Orlov, Sergey; Rumyantsev, Aleksander
Abstract: BACKGROUND AND AIMS: High consumption of NaCl is traditionally considered the cardiovascular risk factor and the blood pressure (BP) growth factor. The considerable sodium content in the diet is associated with myocardium remodelling. Recently, attention has been also paid to studying the impact of high NaCl consumption at the condition of kidneys. However, no mechanisms of potential negative impact of high salt diets on kidneys were established. The microRNA may act as one of the important links in this process. Track changes in microRNA-21, 203 and 133 expression in urine of cynomolgus monkeys at high sodium chloride consumption with and without inclusion of isolated soy proteins into the diet. METHOD: A total of 18 cynomolgus male monkeys with age 6–8 years were studied. The animals were divided into three groups (six in each group). The first (control) group received the standard diet. The second group received the diet rich in common salt (8 g of NaCl/kg), and the third, the high salt diet in combination with soy protein SUPRO 760 (200 g/kg; Protеin Tеchnology Intеrnational, USA). The observation period was 4 months. Determination of the relative level of microRNA expression in urine was performed by isolating total RNA with phenol reagent (Trirеagеnt-LS) and its subsequent extraction with chloroform. The reverse transcription reaction for 'complementary' DNA (cDNA) preparation was carried out under the Stеm Loop technology separately for the studied microRNA. The polymerase chain reaction (PCR) was carried out in the presence of ЕvaGrееn intercalating dye. The following primers were used in PCR: microRNA-21–5`-GCCCGCTAGCTTATCAGACTGATG-3′, microRNA-133–5′-GCCCGCAGCTGGTAAAATGGAAC-3′, microRNA-203–5′- GCCGGTGAAATGTTTAGGACC-3′ and U6–5′-GCGCGTCGTGAAGCGTTC-3′, and common reverse 5′-GTGCAGGGTCCGAGGT-3′. Reaction mixtures were prepared individually for each cDNA. The semi-qualitative evaluation of the microRNA expression level (in relative units, RU) under the 2–ΔΔCt protocol at the laboratory referent (0.09) was used in calculations. RESULTS: No significant changes in microRNA-21 expression during the observation period (the baseline point and 4 months of observation) in the control group ( P < .05). The significant growth approximately to equal extent of this parameter versus baseline values was observed in two other samples in 4 months after receiving the high salt diet. Changes in microRNA-133 or microRNA-203 in studied groups of monkeys were similar to those revealed for microRNA-21. Both high salt diets caused the significant growth in the relative level of expression of these microRNAs in urine versus basal values. At this, the median of the relative level of microRNA-133 expression in monkeys that consumed large amounts of salt for 4 months was significantly higher than in animals at the high salt diet, complemented with soybean isolate ( P = .008; Mann–Whitney test). The similar situation has come about in relation to microRNA-203 ( P = .0065; Mann–Whitney test). CONCLUSION: The data received allow the conclusion that the potentially negative effect of high salt diets on the condition of kidneys can be mediated by epigenomic mechanisms, in particular, changes in the expression of the certain microRNAs. There is a good chance that activation of microRNA-21 expression (which at this term of study is not inhibited by administration of soy proteins) is responsible for renal impairment to the certain extent. It can also be assumed that soy proteins can interfere into this processes and change expression of some microRNAs.